INFORMATION SECURITY IN THE COUNTRIES OF CENTRAL ASIA: THE CASE OF KAZAKHSTAN - Z. A. Asadova (Vestnik MGIMO-Universiteta)
The article discusses the history of the creation and development of the overall concept of information security, the current state of the information security, as well as the appropriate legal and regulatory framework in the countries of Central Asia on the example of the Republic of Kazakhstan. Introductory part of the article analyzes and provides a brief overview of the development of information and communication technologies. Particular attention is given to information security concepts in the framework of international valuation standards. The author investigates and lists the main sources of global information security threats, as well as explaining the history of the creation of a geopolitical term - Central Asia. In the main part of the article on the example of Kazakhstan one of the leading Central Asian countries, highlights issues of formation and development of the concept of information security, provides a brief overview of the history of development of information and communication technologies in the country. In this part the author conducts a detailed analysis of the legislation and the concept of the state with respect to the issue of information security, in the investigation highlights the major key issues of information security in the Republic of Kazakhstan. It also analyzes the development strategy of the Republic of Kazakhstan till 2030 (the "Kazakhstan-2030" Strategy), provides a brief overview of the state of laws and programs in the field of information security in the Republic of Kazakhstan. In conclusion, the author comes to the conclusion that today Kazakhstan is just beginning to form their own information security protection mechanisms and leads appropriate recommendations to achieve the objectives of the state.